Characterization of immunological properties of chicken chemokine CC motif ligand 5 using new monoclonal antibodies. (June 2021) - Lu, Mingmin; Panebra, Alfredo; Kim, Woo H.; Lillehoj, Hyun S.
Abstract: CCL5 (formerly RANTES) belongs to the CC (or β) chemokine family and is associated with a plethora of inflammatory disorders and pathologic states. CCL5 is mainly produced and secreted by T cells, macrophages, epithelial cells, and fibroblasts and acts as a chemoattractant to recruit effector cells to the inflammation sites. Chicken CCL5 (chCCL5) protein is closely related to avian CCL5 orthologs but distinct from mammalian orthologs, and its modulatory roles in the immune response are largely unknown. The present work was undertaken to characterize the immunological properties of chCCL5 using the new sets of anti-chCCL5 mouse monoclonal antibodies (mAbs). Eight different mAbs (6E11, 6H1, 8H11, 11G1, 11G11, 12H1, 13D1, and 13G3) were characterized for their specificity and binding ability toward chCCL5. Two (13G3 and 6E11) of them were selected to detect native chCCL5 in chCCL5-specific antigen-capture ELISA. Using 13G3 and 6E11 as capture and detection antibodies, respectively, the ELISA system detected serum chCCL5 secretions in Clostridium perfringens - and Eimeria -infected chickens. The intracellular expressions of chCCL5 in primary cells or cell lines derived from chickens were validated in immunocytochemistry and flow cytometry assays using both 13G3 and 6E11 mAbs. Furthermore, 6E11, but not 13G3, neutralized chCCL5-induced chemotaxis in vitro using chicken PBMCs. These molecular characteristics of chCCL5 demonstrate the potential application of anti-chCCL5 mAbs and CCL5-specific antigen-capture detection ELISA for detecting native chCCL5 in biological samples. The availability of these new immunological tools will be valuable for fundamental and applied studies in avian species. Highlights: ChCCL5 is closely related to avian CCL5 orthologs but different from mammal orthologs. An antigen-capture ELISA was developed to detect native chCCL5 in serum from C. perfringens - and Eimeria -infected chickens. Endogenous chCCL5 expression was validated by immunocytochemistry and flow cytometry assays using anti-chCCL5 mAbs. The chemotactic activity of chCCL5 was neutralized by an anti-chCCL5 mAb.